Severe anaemia in people with HIV: demographic, clinical and renal correlates - Kingsley Kamvuma; Sody Munsaka; Sepiso K. Masenga; John Amos Mulemena; Christopher Newton Phiri; Michelo Miyoba; Benson M. Hamooya (BMC Research Notes, 2025)
Abstract Objective This study aimed to investigate the sociodemographic, clinical and renal correlates associated with severe anaemia among people with HIV. Methods We conducted a cross-sectional analysis of people with HIV on antiretroviral therapy (ART) for at least 6 months, stratified by anaemia status. Anaemia was defined based on the World Health Organisation (WHO) classification, as haemoglobin concentration lower than normal i.e. <12 g/dl in females and < 13 g/dl in males and the primary outcome, severe anaemia, as a haemoglobin level below 8 g/dl according to the World Health Organisation. Results The study comprised 372 participants receiving ART, of whom 236 (63.4%) were females. The mean age ± SD of the participants was 44.8 ± 12.4 years. The overall prevalence of severe anaemia was 7.8% (95% CI: 0.053–0.111). In multivariable logistic regression analysis, factors significantly associated with severe anaemia were female sex (Adjusted Odds Ratio (AOR: 14.3, 95% CI: 2.14–126.6), albumin (AOR: 0.93 95% CI: 0.88–0.98) and creatinine levels (AOR: 1.01 95% CI: 1.00-1.03).